Matera soundscapes. Design research workshop. - (:unkn) unknown (My University, 2019)
The international workshop Matera Soundscapes explores sound as a new tool of urban design and a platform for urban visions. Matera Soundscapes aims to extend articulated acoustic perceptions of a city into devices of design and to conceive soundscapes as stages of urban performativity that encompass new ways of interaction and involvement: to think about and engage with architecture and space through sound. The workshop is part of the "Sounds of the Remote Future", a cross-disciplinary project coproduced by Onyx Jazz Club Matera and MateraBasilicata2019 Foundation. DiCem University of Basilicata and Leibniz Universität Hannover are the academic partners. Through merging urban design, performance studies, approaches of visual sociology, anthropology, and acoustic arts, the workshop aims at tangilble and intangible interaction of sound, form, space, and body. In a design research approach, Matera Soundscapes extends material-virtual cultural and artistic creativity towards dynamics of urban transformation.
Keywords: Stadtsoziologie; Stadtentwicklung; Stadtstruktur; Klang; Urban Design; Stadtgestaltung; Historische Stadt; Forschungsprojekt